Speech Acts and Pragmatic in Multilingual and Multicultural Settings - Rosa Anjani; Rizki Tiara Ayunda; Widya Maharani; Dela Wahyuni; Deasy Yunita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This study investigates speech acts and pragmatics in Indonesia’s multilingual and multicultural settings, focusing on how linguistic diversity and cultural norms influence communication strategies. Using a qualitative approach, data were collected through interviews, ethnographic observations, and discourse analysis involving participants from various cultural backgrounds, including Bataknese and Sundanese communities. The study examines requests, apologies, and refusals, exploring how these speech acts reflect cultural values and adapt to different social hierarchies and contexts. The findings highlight that Bataknese speakers often use direct language, emphasizing clarity, while Sundanese speakers prefer indirectness and elaborate politeness to maintain harmony. Code-switching emerged as a significant strategy, allowing participants to navigate linguistic and cultural boundaries effectively, often shifting between Indonesian, local languages, and English depending on the audience and context. Additionally, in digital communication, pragmatic strategies evolved with the use of emojis, formal expressions, and explanations to ensure clarity and respect. These results underscore the dynamic and adaptable nature of pragmatic competence in multilingual and multicultural contexts, offering insights into the interplay of language and culture. This research contributes to the broader understanding of communication in diverse settings, providing valuable implications for intercultural interactions in education, business, and social integration Keywords: Speech act, Pragmatic, Multilingualism, Cultural Norms